LOW BIRTH WEIGHT IN TWIN BABIES: CASE STUDY AND CLINICAL MANAGEMENT - Marpaung, Intan Maharani; Rosmani Sinaga; Triwahyu Aulia; Plora Novita Febrina Sinaga; Tivani Seprine Tampubolon; Syahrin Sakinah Haslim; Sumita Ramadani (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Twin pregnancies are inherently high-risk gestations frequently associated with Low Birth Weight (LBW) due to uterine capacity limits and nutrient competition. LBW remains a primary contributor to neonatal morbidity and mortality globally, including in Indonesia. Objective: This study aims to evaluate the implementation of integrated midwifery care using the 7-step Helen Varney framework in managing twin neonates with LBW to optimize clinical outcomes. A qualitative descriptive case study was conducted on a 30-year-old multigravida mother and her twin neonates born at 36^+4 weeks of gestation. Data were collected through longitudinal observation, physical examinations, and semi-structured interviews. Clinical management followed the systematic Helen Varney framework, benchmarking outcomes against national neonatal care standards. Baby A (2100g) and Baby B (1900g) were born with high vitality (Apgar scores 8-10) despite their LBW status. The primary etiologies identified were maternal nutritional deficits and placental insufficiency. Immediate interventions, including thermal regulation, Vitamin K prophylaxis, and early initiation of exclusive breastfeeding, resulted in steady weight gain and the absence of postnatal complications. Conclusion: Integrated midwifery care and the Continuity of Care (CoC) model are essential in mitigating the risks associated with twin LBW. Standardizing systematic frameworks in primary healthcare settings can significantly improve neonatal survival and long-term growth trajectories.